Houses for aging socially : developing third place ecologies - University of Arkansas, Fayetteville. Community Design Center (2017)
"Third place ecologies reworks components of the familiar single-family home to promote new levels of connectivity in neighborhoods once resistant to sharing. Individual porches are extended in order to serve multiple units as hyper-porches, garage galleries hydridize car parking to become neighborhood work and maker spaces, and patio mats are used as live-work venues all to revitalize neighborhoods through return of the informal." - back cover.
Introduction : Housing as a social context for aging / Stephen Luoni -- A gerontological framework for new senior living models / Alexis Denton -- Shared space and the shared economy / Thomas Fisher -- Place in aging: a brief note on Michael Haneke's Amour / Daniel Friedman -- Rethinking aging and housing -- Why aging? Why so disruptive? -- City + culture -- Introducing third place fabrics : Hyper-porch ; Patio mat ; Garage gallery -- Retrofitting existing fabric.
Includes bibliographical references (pages 138-143).
Keywords: 2000-2099; Older people -- Housing; Housing policy; Architecture, Domestic -- 21st century -- Designs and plans; Baby boom generation; Older people -- Housing; Housing policy; Baby boom generation; Architecture, Domestic; Baby boom generation; Housing policy; Older people -- Housing; Freeman (S.D.); Freeman (S.D.); South Dakota -- Freeman; South Dakota -- Freeman; Architectural drawings; Architectural drawings